PENGARUH TERAPI BERMAIN TERHADAP PENURUNAN KECEMASAN PADA ANAK USIA PRA SEKOLAH - Delfina, Rina (JURNAL MEDIA KESEHATAN, 2017)
The hospital treatment experienced by a child can lead to a variety of experiences that are very traumatic and full of anxiety. Anxiety that can arise can be caused by many factors such as the physical environment of the hospital, among others, room care, tools, smells typical, white clothing health workers and the environment. The purpose of this study was to see the effect of play therapy on decreased anxiety of preschool children who were treated. The type of research is quasy experiments using the one group pretest-postest design. The sample of the study was pre-school age children who were treated in edelwiss RSUD Dr. M. Yunus Bengkulu. Data collection using observation sheets. Quantitative data analysis is univariate and Bivariate with Paired T-Test. The results showed that there was an effect of playing therapy on anxiety reduction in pre-school age children treated (ρ = 0.000). To the hospital to further improve playing therapy activities for children who are treated in an effort to reduce anxiety in children.